Intelectuais brasileiros e as representações do (sub) desenvolvimento como projeto de educação : o Instituto Superior de Estudos Brasileiros (ISEB) na década de 1950 - Santos, Cleber Ferreira dos (2018)
This research has as main objective to understand how a group of intellectuals, immersed in the development policy of the 1950s in Brazil, represented, through the Institute of Brazilian Studies (ISEB), the problem of (Sub) development as an education project . Since this is a historical study, as a research source, we will privilege a document described as the Successful Activity Report of the ISEB, emphasizing the classes that were given and published, between 1956 and 1960, in order to understand the role occupied by Education in Brazilian development policy in that period. For this, we use the conceptual scheme of Roger Chartier (1990, 1991, 2002, 2007): representation, circulation and appropriation. In dialogue with Jean-Francois Sirinelli (2000), we understand the engagement of the intellectual in the problematic of his time. Already in the search for the understanding of the political / cultural field that the intellectuals of the ISEB were inserted, we will highlight Pierre Bourdieu (2000) and Reinhart Koselleck (2006), in order to understand the main themes that designed the Isebian politics from his project of Education.